Functionalized Doubly Porous Networks: From Synthesis to Application in Heterogeneous Catalysis. Issue 1 (July 2016) - Ly, Hai Bang; Poupart, Romain; Halbardier, Lucile; Grande, Daniel
Summary: This paper addresses the functionalization of doubly porous poly(2‐hydroxyethyl methacrylate) (PHEMA)‐based networks obtained from the double porogen approach, and their subsequent utilization as catalytic supports in heterogeneous catalysis. Advantage of the availability of hydroxyl groups within the PHEMA‐based frameworks was taken through a chemical modification with carbonyldiimidazole. This key activation led to three main functionatization reactions of the materials via nucleophilic substitution or thiol‐yne "click" addition of amino molecules. Further, in‐situ generation of gold nanoparticles (GNPs) allowed for the preparation of innovative functionalized biporous GNP@PHEMA materials. The as‐obtained hybrid frameworks could efficiently be used as catalytic supports in the reduction of 4‐nitrophenol.